2007
DOI: 10.1002/qj.25
|View full text |Cite
|
Sign up to set email alerts
|

A modelling study of aerosol impacts on cloud microphysics and radiative properties

Abstract: A warm cloud microphysical parameterization was incorporated into a regional model to study the sensitivity to aerosols of cloud-radiative properties and precipitation. Assuming a trimodal lognormal aerosol size distribution, the aerosol numbers were explicitly calculated from prognostic aerosol masses, considering advection, diffusion, and cloud and raindrop activation/deactivation processes. Clean continental, average continental and urban aerosols, each with different modal parameters, were used to serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…For example, Lynn et al (2005) found that precipitation processes and rainfall were suppressed by enhancing the aerosol concentration for a Florida squall line. Cheng et al (2007) also found that increasing aerosols inhibited precipitation for a Oklahoma warm cloud system.…”
Section: F Aerosol-precipitation Interactive Processesmentioning
confidence: 86%
“…For example, Lynn et al (2005) found that precipitation processes and rainfall were suppressed by enhancing the aerosol concentration for a Florida squall line. Cheng et al (2007) also found that increasing aerosols inhibited precipitation for a Oklahoma warm cloud system.…”
Section: F Aerosol-precipitation Interactive Processesmentioning
confidence: 86%
“…Additional case studies addressing microphysical and PBL processes, including more comprehensive microphysical sensitivity testing (e.g., turning off certain conversion processes from one cloud species to another), will be considered in future research. Recently, a spectral bin microphysics scheme (Khain et al 2004) and a two-moment scheme (Cheng et al 2007) were implemented into WRF; additional sensitivity tests with these sophistical microphysical schemes will be needed. Sensitivity tests on model resolution (horizontal grid spacing from 1 up to 5 km * , and 31 to 81 vertical layers), terrain height (lifting and blocking, see discussion in section 4) and sea surface temperature (surface latent heat fluxes, see discussion in section 5.2) will be conducted and discussed in Part II.…”
Section: Discussionmentioning
confidence: 99%
“…This drives a delay in rain formation and can affect the amount of surface rain (Rosenfeld, 1999(Rosenfeld, , 2000Cheng et al, 2007;Khain, 2009;Levin and Cotton, 2009;Koren et al, 2012;Hazra et al, 2013a, b;Dagan et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%